PILOTING A VIRTUAL REALITY APPLICATION TO PROMOTE EXECUTIVE FUNCTION AND COMMUNITY MOBILITY IN AGING ADULTS. (11th November 2018) - Carlson, M; Chan, T; Adam, A; Ahmad, O; Roy, P; Rosano, C; Rosso, A; Krakauer, J
Abstract: We adapted and optimized an immersive simulated reality game developed for rehabilitation of upper extremity function after stroke for complex, cognitive-motor training in a community setting for older adults to promote executive functions and independent physical function. Using a Microsoft Kinect system, participants controlled the movement of a dolphin displayed on large screen as a 3-dimensional oceanic environment by performing a complex combination of skilled arm movements to achieve varying levels of cognitive challenge (catch fish, jump and flip). Participants played the game, entitled, Stimulation With Intricate Movements (SWIM), 90–120 min./week for 6 weeks relative to an active control group who exercised with a hand bike over an equivalent exposure. Adults found the SWIM game to be aerobic given the continuous and sweeping arm movements required. We will summarize the short-term feasibility and results on computerized measures of executive function, processing speed, and gait speed across conditions.